Penggunaan Program Trauma-Focused - Cognitive Behavioral Therapy untuk anak dengan Adverse Childhood Experiences - Diella Gracia Martauli Hutasoit; Indri Hapsari (Psikostudia : Jurnal Psikologi, 2024)
Adverse Childhood Experiences (ACEs) are distressing events encountered during childhood that can have long-term negative impacts on physical and mental health. This study examines an intervention provided to a 7-year-old girl who faced ACEs in her daily life. The ACEs experienced by the participant were categorized into six conditions: emotional abuse, physical abuse, witnessing maternal violence, household substance abuse, mental illness in the household, and emotional neglect. The intervention used an adapted Trauma-Focused Cognitive Behavioral Therapy (TF-CBT) approach to address social-emotional issues. Three main areas were targeted, including social-emotional problems, attachment, and resilience. The effectiveness of the intervention was assessed using 2 measures: the Strengths and Difficulties Questionnaire (SDQ) and the Child Behavior Checklist (CBCL). The intervention program consisted of 7 weekly sessions with activities tailored to the participant’s talents and interests, including journaling, crafts, making playdough, painting, and playing. Results indicated that the adapted TF-CBT approach effectively facilitated behavioral changes in children with ACEs in the social-emotional domain, as evidenced by both quantitative scores and qualitative interviews with the participant and her parents. Despite its effectiveness in reducing externalizing behaviors, such as temper tantrums, an increase in internalizing behaviors, such as withdrawal, was observed. This suggests the need for further evaluation and follow-up treatment.Adverse Childhood Experiences (ACEs) adalah pengalaman tidak menyenangkan yang dialami oleh seseorang ketika kecil, yang berisiko memberikan dampak buruk jangka panjang terhadap kesehatan fisik dan mental. Penelitian ini membahas intervensi yang diberikan kepada seorang partisipan anak perempuan usia 7 tahun yang mengalami ACEs dalam kesehariannya. ACEs yang dialami oleh partisipan tergolong ke dalam 6 kondisi, yakni emotional abuse, physical abuse, mother treated violently, household substance abuse, mental illness in household, serta emotional neglect yang dilakukan oleh ayah. Intervensi yang digunakan mengadaptasi pendekatan Trauma – Focused Cognitive Behavior Therapy untuk menangani masalah sosial emosional. Terdapat tiga area utama yang ingin disasar, yakni masalah sosial emosional, attachment dan resiliensi. Asesmen yang digunakan untuk melihat efektivitas intervensi adalah Strengths and Difficulties Questionnaire (SDQ) dan The Child Behavior Checklist (CBCL). Program intervensi terdiri atas 7 sesi, dengan frekuensi satu kali dalam seminggu. Kegiatan yang dilakukan dirancang sesuai dengan talenta dan minat partisipan, seperti journaling, prakarya, membuat playdough, melukis dan bermain. Hasil intervensi menunjukkan bahwa adaptasi pendekatan Trauma-Focused Cognitive Behavior Therapy dapat digunakan untuk membantu mewujudkan perubahan perilaku anak dengan ACEs dalam area sosial emosional, yang tergambar dari skor kuantitatif dan wawancara kualitatif dengan partisipan serta orang tua. Meski intervensi ini efektif dalam mengurangi kecenderungan externalizing seperti mudah marah, namun ditemukan peningkatan perilaku internalizing seperti kecenderungan menarik diri sehingga dibutuhkannya evaluasi dan penanganan lanjutan.